2003
DOI: 10.1002/hlca.200390340
|View full text |Cite
|
Sign up to set email alerts
|

Outlying Charge, Stability, Efficiency, and Algorithmic Enhancements in the Quantum‐Mechanical Solvation Method, COSab‐GAMESS

Abstract: This and the companion paper are dedicated to Professor Duilio Arigoni on the occasion of his 75th birthday.His steadfast work focused on the structure and biosynthesis of natural products, and mechanisms and stereochemistry of related biochemical processes, foreshadows important insights in our own investigations presented here.In this work, we present algorithmic modifications and extensions to our quantum-mechanical approach for the inclusion of solvent effects by means of molecule-shaped cavities. The theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…NPE solvers that employ the continuous charge density (without approximating it by distributed point charges or multipoles) will be further called density-based solvation models. An example of such models is the polarizable continuum model (PCM). , Various PCM formulations include the integral-equation-formalism protocol (IEF-PCM), the dielectric version of PCM (D-PCM), ,, and the conductor-like screening algorithm. It has been shown that the IEF-PCM formalism is equivalent to the SS(V)PE method of Chipman . Other implicit solvation models solve the NPE using alternative representations of the continuous density, for example, single- or multicenter multipolar expansions. An alternative continuum model, the generalized Born (GB) approximation, does not start with the NPE, but instead employs a starting point based on Coulomb’s law and represents the solute as a collection of point charges (a distributed monopole approximation), located at the nuclear positions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NPE solvers that employ the continuous charge density (without approximating it by distributed point charges or multipoles) will be further called density-based solvation models. An example of such models is the polarizable continuum model (PCM). , Various PCM formulations include the integral-equation-formalism protocol (IEF-PCM), the dielectric version of PCM (D-PCM), ,, and the conductor-like screening algorithm. It has been shown that the IEF-PCM formalism is equivalent to the SS(V)PE method of Chipman . Other implicit solvation models solve the NPE using alternative representations of the continuous density, for example, single- or multicenter multipolar expansions. An alternative continuum model, the generalized Born (GB) approximation, does not start with the NPE, but instead employs a starting point based on Coulomb’s law and represents the solute as a collection of point charges (a distributed monopole approximation), located at the nuclear positions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the SMD parameters may also be used with other algorithms for solving the NPE in which the solute is represented by its electron density in real space. This includes, for example, the conductor-like screening algorithm called, in various implementations, which sometimes differ in details, COSMO, generalized COSMO (GCOSMO), COSab, conductor-like PCM (CPCM or C-PCM), or CD-COSMO. Here we use C-PCM to label the implementations called C-PCM in Gaussian03 and GAMESS, and we use COSMO to label the implementation called COSMO in NWChem . C-PCM and COSMO solve the nonhomogeneous Poisson equation for an infinite dielectric constant (corresponding to the solvent being a conductor rather than a dielectric) but with scaled dielectric boundary conditions in order to approximate the result for a finite dielectric constant; this is a better approximation at high dielectric constant (e.g., 80) than at low dielectric constant (e.g., below 10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All calculations were performed with the GAMESS electronic structure program . Full optimizations were carried out including effects of solvation via the DSES-CC model, using B97-D/6-311+G­(2d,p)/COSab, with our most recent implementation of COSab solvation model. Parameter optimization for several combinations of DFT functional type and basis sets have been carried out within the solvation model in previous work . In our initial development of the DSES-CC model, investigation covering basis set, wave function type, thermodynamic cycle, reaction scheme, and solvent parameters were carried out .…”
Section: Methodsmentioning
confidence: 99%
“…Dielectric permittivity of water (ε = 78.4) was used, with cavity parameters of 1082 points for the basic grid, 92 segments on the complete sphere. Outlying charge error correction was taken into account via the double cavity approach . DSES-CC representations were depicted using MacMolPlt …”
Section: Methodsmentioning
confidence: 99%